Plant-based and cell-based approaches to meat production - Rubio, Natalie R.; Xiang, Ning; Kaplan, David L. (Nature communications, 2020)
Advances in farming technology and intensification of animal agriculture increase the cost-efficiency and production volume of meat. Thus, in developed nations, meat is relatively inexpensive and accessible. While beneficial for consumer satisfaction, intensive meat production inflicts negative externalities on public health, the environment and animal welfare. In response, groups within academia and industry are working to improve the sensory characteristics of plant-based meat and pursuing nascent approaches through cellular agriculture methodology (i.e., cell-based meat). Here we detail the benefits and challenges of plant-based and cell-based meat alternatives with regard to production efficiency, product characteristics and impact categories. Large-scale meat production can have negative impacts on public health, the environment and animal welfare. In this Review, the authors consider plant-based and cell-based approaches to meat production and the challenges they face.